2015
DOI: 10.11622/smedj.2015057
|View full text |Cite
|
Sign up to set email alerts
|

Renal-related adverse effects of intravenous contrast media in computed tomography

Abstract: Renal-related adverse effects of intravascular contrast media (CM) include contrast-induced nephropathy in computed tomography and angiography. While large retrospective studies have been published, the exact pathogenesis of this condition is still unknown. We review the main international guidelines, including the American College of Radiology white paper and the guidelines of European Society of Urogenital Radiology, Royal College of Radiologists and Canadian Association of Radiologists, as well as their ref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 68 publications
0
23
0
Order By: Relevance
“…There are distinct types of complications following intravenous use: soft tissue injury, direct chemical toxicity, nephrotoxicity, and anaphylactic reactions (Leow et al 2015 ; Li et al 2015 ; McAlister and Kissane 1990 ). Nearly 2 % of the patients in this study experience adverse reactions related with intravenous contrast medium, similar to the dictation of Ho et al (Ho et al 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…There are distinct types of complications following intravenous use: soft tissue injury, direct chemical toxicity, nephrotoxicity, and anaphylactic reactions (Leow et al 2015 ; Li et al 2015 ; McAlister and Kissane 1990 ). Nearly 2 % of the patients in this study experience adverse reactions related with intravenous contrast medium, similar to the dictation of Ho et al (Ho et al 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…It was found that the oxidation current peak of AA at 600 mV effected on the redox current peaks of the contrast medium, causing the disappearance of anodic (oxidation) current peak of the contrast medium and the enhancement of cathodic (reduction) current peak at -900 mV. Hence, AA acted as an electrocatalyst reagent for safely using gadolinium compounds in blood medium [26][27][28][29].…”
Section: Effect Of Gadolinium Compound In Blood Mediummentioning
confidence: 99%
“…As such, it may be useful to guide valve selection in low-resource settings where access to MSCT or TEE technology is limited. Furthermore, given that only a fraction of the contrast agent used for MSCT was required for CA, the latter approach may be an interesting alternative for patients at high risk of contrast-induced nephropathy 28. As always, a balance must be struck between the risks and benefits of each technique.…”
Section: Discussionmentioning
confidence: 99%